2021
DOI: 10.3389/fonc.2021.770500
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Contributions to Prostate Cancer Disparities in Men of West African Descent

Abstract: Prostate cancer (PCa) is the second most frequently diagnosed malignancy and the second leading cause of death in men worldwide, after adjusting for age. According to the International Agency for Research on Cancer, continents such as North America and Europe report higher incidence of PCa; however, mortality rates are highest among men of African ancestry in the western, southern, and central regions of Africa and the Caribbean. The American Cancer Society reports, African Americans (AAs), in the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 150 publications
0
15
0
Order By: Relevance
“…Moreover, AA prostate cancer patients present with higher grade and stage tumors and have a nearly 2-fold higher mortality rate when compared to EA prostate cancer patients (2). Specifically, AA men have a prostate cancer mortality rate of 37.4 per 100,000 in the period of 2014-2018 versus 19.3 per 100,000 among white non-Hispanic men (3). Furthermore, prostate cancer has a higher growth and metastatic transformation rate for AA men compared to EA men (4).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, AA prostate cancer patients present with higher grade and stage tumors and have a nearly 2-fold higher mortality rate when compared to EA prostate cancer patients (2). Specifically, AA men have a prostate cancer mortality rate of 37.4 per 100,000 in the period of 2014-2018 versus 19.3 per 100,000 among white non-Hispanic men (3). Furthermore, prostate cancer has a higher growth and metastatic transformation rate for AA men compared to EA men (4).…”
Section: Introductionmentioning
confidence: 99%
“…A striking PCa disparity was observed, where African Americans (AAs) demonstrate a 1.7-fold higher incidence rate and a 2.3-fold higher mortality rate compared to their European American (EA) counterparts [ 1 ]. Besides the socioeconomic factors, accumulating genomic studies have suggested that genetic risk factors may also be involved in the PCa disparities [ 2 , 3 , 4 , 5 ]. MicroRNAs (miRNAs) are short non-coding RNAs regulating protein expression through degradation of target mRNAs or inhibition of protein translation.…”
Section: Introductionmentioning
confidence: 99%
“…Even after adjusting for nonbiological factors, prostate cancer mortality rates remain significantly higher in AA men than in CA. 6,7 A 5-year analysis revealed a 73% higher incidence rate and more than two times higher deaths due to prostate cancer in AA than in CA men. 2 Therefore, various biological factors, including the high systemic levels of inflammatory exposure associated with differential allostatic load, 8,9 may account for aggressive prostate cancer by altering tumor-specific immunobiology in AA men.…”
Section: Introductionmentioning
confidence: 99%